II. Abdülhamid dönemi Trablusgarb Vilayeti Islahat Lâyihaları - Deniz, Taģan (My University, 2016)
I.Abdülhamid’e sunulan çok sayıdaki lâyiha içinden 19. yüzyılın ikinci yarısında Trablusgarp’a dair ıslahat lâyihalarının başlıcaları bu araştırmada bir araya getirilerek gerek orijinal belgelerin suretleri, gerekse transkripsiyonları sunulmaktadır. Bu lâyihalar, sosyal, iktisadi ve idari yapı özelliklerine göre tasnif edilerek değerlendirilmiştir. Böylece, 19. yüzyılın ikinci yarısında, arşiv belgelerine dayalı olarak Trablusgarp’ın sosyal yapısına ışık tutulmaya çalışılmıştır. Dönemin valilerinden bazıları hakkında ansiklopedilerde geniş bilgi bulunmasına rağmen, II. Abdülhamid dönemi valilerin çoğu hakkında literatürde pek az bilgi vardır. Bu tez, bu konudaki eksiklik arşiv belgelerine dayalı bilgilerle gidermeye gayret etmektedir. Trablusgarp, ıslahat, lâyiha, vali, II. Abdülhamid, Ahmet Rasim Paşa

Many reform proposal treatises regarding Trablusgarb (Tripoli) in the second half of the 19th century were submitted to Abdulhamid II and the main proposals have been collected in this thesis. They are presented in the form of texts written in Ottoman Turkish and, also, in the form of transcriptions in modern Turkish. These reform proposal treatises are classified and evaluated according to their social, economic and administrative features. Thus, it is intended to enlighten the social structure of Tripoli in the second half of the 19th century based on the Ottoman archive documents. Although there is adequate information about some governors of the era in encyclopedias, there is little information regarding most of the governors of the era of Abdulhamid II in the relevant literature. This thesis tries to fill this gap by making use of the Ottoman archives. Trablusgarp (Tripoli), reform, reform proposal treatise, governor, Abdulhamid II, Ahmet Rasim Pasha.
Keywords: II. Abdülhamid dönemi; Osmanlı İmparatorluğu; Tarih; Trablusgarp